ANALISIS WACANA KRITIS POPULISME PARTAI KEADILAN SEJAHTERA DALAM MENDORONG PENGESAHAN RKUHP DENGAN SENTIMEN ANTI LGBT+ DI TWITTER - Luthfi Maulana Adhari; Triyono Lukmantoro; Nurul Hasfi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
This research is anchored in the discourse of the Prosperous Justice Party (PKS), which advocates for the enactment of the Criminal Code that entails the criminalization of LGBT+ groups within the virtual public space of Twitter. The primary objective of this study is to elucidate how populist discourse is strategically employed in the Twitter virtual text disseminated via the @PKSejahtera account, as well as the responses of users who engage with these tweets. Critical discourse analysis is employed as the analytical framework to scrutinize the tweets, with the research corpus consisting exclusively of @PKSejahtera tweets that discuss the Criminal Code and LGBT+ issues during the period between May and December 2022. The author relies on the critical discourse analysis methodology developed by Christian Fuchs, which specifically examines discourse texts within the Twitter platform. The research findings unveil the utilization of populist ideology by the Prosperous Justice Party, accompanied by additional discourses such as legal and political discourse, social discourse, and religious discourse, all aimed at promoting the ratification of the Criminal Code through the cultivation of negative sentiments towards the LGBT+ community, underpinned by discourses that advocate for punitive measures against them. Among these three discourses, the Prosperous Justice Party primarily relies on legal and political discourse to advocate for the adoption of the Criminal Code that encompasses penalties for LGBT+ individuals. Meanwhile, religious discourse is predominantly utilized in interactive exchanges, all of which support the discourse propagated by the Prosperous Justice Party. The conflicting discourses that emerge primarily originate from legal and political discourse. Furthermore, the interactivity of these tweets reveals the existence of several contradictory discourses that stand in opposition to the discourse propagated by the PKS. Nevertheless, the prevailing trend within this interactivity is the dominance of discourses aligned with the majority ideology that harmonize with the PKS's agenda to pass the Criminal Code, which includes provisions pertaining to the punishment of LGBT+ individuals.